(1003) Manpower Planning in Egypt: Techniques and Major Results تخطيط القوى العاملة في مصر: التقنيات والنتائج الرئيسية - Abdel Fattah Nassef. (INP., 2020)
Labor force occupies a central role in the productive process. Lands and capital are essential for production, yet it is the human factor that gives them such essential value. Hence, manpower development is a major target in the overall socio-economic development